2004
DOI: 10.1097/01.gim.0000139507.20179.3a
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype correlation and frequency of the 3199del6 cystic fibrosis mutation among I148T carriers: Results from a collaborative study

Abstract: Purpose: We expect that the mutation panel currently recommended for preconception/prenatal CF carrier screening will be modified as new information is learned regarding the phenotype associated with specific mutations and allele frequencies in various populations. One such example is the I148T mutation, originally described as a severe CF mutation. After implementation of CF population-based carrier screening, we learned that I148T exists as a complex allele with 3199del6 in patients with clinical CF, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…This behavior is inconsistent with the latter mutations being causative of CF and suggests that they are instead benign CFTR variants. In fact, it has been shown that I148T is in linkage disequilibrium with a deletion of two amino acids (3199del6) localized more distantly toward the carboxyl terminus (Rohlfs et al, 2002;Monaghan et al, 2004) and that this latter sequence change is the one causing CFTR loss of function. I175V may be another benign variant because its activity was comparable with or even higher than that of the native protein.…”
Section: Discussionmentioning
confidence: 99%
“…This behavior is inconsistent with the latter mutations being causative of CF and suggests that they are instead benign CFTR variants. In fact, it has been shown that I148T is in linkage disequilibrium with a deletion of two amino acids (3199del6) localized more distantly toward the carboxyl terminus (Rohlfs et al, 2002;Monaghan et al, 2004) and that this latter sequence change is the one causing CFTR loss of function. I175V may be another benign variant because its activity was comparable with or even higher than that of the native protein.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, our observations further demonstrate that the 3199del6 mutation is associated with a classical pancreatic insufficiency CF phenotype, consistent with the suggestion of Buyse et al 7 Previous studies have identified 3199del6 in 1.8%, 0.9%, and 0.6% of I148T heterozygous carriers and determined the frequency of 3199del6 in the general North American population to be Ͻ 0.1%, below the frequency threshold criteria for inclusion in the ACMG CF mutation screening panel. 1,8,9 In this study, we report a 2.2% frequency for the 3199del6 mutation among French Canadian CF chromosomes. As mentioned, only two I148T carriers (one Lebanese and one of unknown origin) tested negative for the 3199del6 mutation in our cohort of 32 unrelated I148T individuals.…”
Section: Frequency and Phenotypic Consequences Of The 3199del6 Cftr Mmentioning
confidence: 94%
“…Consequently, alternative and simpler direct pancreatic stimulation techniques (non-quantitative), are used at many clinical centers. These generally utilise a single-lumen duodenal tube or endoscope to aspirate duodenal pancreatic secretions, either as a spot sample and/or over a timed sampling period (Choi et al, 2001;Monaghan et al, 2004;Rohlfs et al, 2002;Suaud et al, 2007). Despite their popularity, non-quantitative techniques have a high false positive rate for misdiagnosing PI and have not been proven superior over non-invasive indirect pancreatic function tests.…”
Section: Pancreatic Function Testingmentioning
confidence: 99%